Re-assessing the International Nuclear non-roliferation regime: a comparison between India and North Korea - Chen, Mumin (Penerbit UKM, 2011)
India’s nuclear tests in 1998 greatly challenged the existing international nuclear non-proliferation regime that had been carefully maintained by the international community since the 1960s. Yet, what is surprising is the response from the international community. Although major world powers imposed sanctions on India, those sanctions were relatively moderate and were lifted over the course of the next few years. More strikingly, in August 2007, India and the United States reached an agreement on civilian nuclear cooperation, effectively ratifying India’s admission to the nuclear club of nations, despite earlier US criticism of India’s moves to go nuclear. Critics of the India-US deal argue the US handling of Indian nuclearization greatly undermine attempts by the international community to prevent other states such as the Democratic People’s Republic of Korea (DPRK, North Korea) from acquiring nuclear weapons, which in turn may potentially contribute to a nuclear arms race in Asia. In fact, international responses to India’s and North Korea`s nuclear programs present opposite approaches in dealing with nuclear proliferation. While most countries from the international community, particularly the U.S., have ultimately recognized India’s nuclear-power status following its 1998 nuclear test, they have taken a much harder line towards North Korea following its nuclear tests in 2006 and 2009. By making a comparison between these two cases, this article assesses the effectiveness of the existing international nuclear non-proliferation regime, and discusses the potential problems associated with the Indian and North Korean acquisition of nuclear weapons.